-4
2006-11-07 18:26:40
·
answer #1
·
answered by Naveen 2
·
0⤊
0⤋
(1 + i)^2 = 1 + 2i - 1 = 2i
2006-11-08 02:34:19
·
answer #2
·
answered by Dr. J. 6
·
0⤊
0⤋
(1 + i)^2 = 1 + 2i - 1 = 2i
Get your teacher to show you phasors. Raising a complex number to a power is similar to a rotation in the complex plane.
2006-11-08 02:28:22
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
i think the question will be (1+i)^2 only then will it be 2i
as 1+i^2+2i = 1-1+2i = 2i
2006-11-08 02:06:50
·
answer #4
·
answered by yog 2
·
1⤊
0⤋
(1+i)^2=1+2i+(i)^2
1+2i-1=2i
2006-11-08 02:13:31
·
answer #5
·
answered by raj 7
·
0⤊
0⤋
Yeah, what yog said!
( i + i ) ² = -1 -1 -1 - 1 = -4
( 1 + i ) ² = 1 + i + i - 1 = 2i
2006-11-08 02:11:39
·
answer #6
·
answered by Helmut 7
·
0⤊
0⤋
(i+i)²
= (2i)²
= 2²x-1
= -4
This is not 2i because i is the squareroot of -1 not just -1.
2006-11-08 04:58:31
·
answer #7
·
answered by Jay 4
·
0⤊
0⤋
nope.You forgot to square.
( i + i ) ² =(2i)^2=-4
2006-11-08 02:18:23
·
answer #8
·
answered by yupchagee 7
·
0⤊
0⤋